THE EFFECT OF NUMBER OF CUSTOMERS AND FUND OF THIRD PARTIES (DPK) ON THE PROVISION OF CASH IN BNI SHARIA YOGYAKARTA BRANCH PERIOD 2008-2010 - Revita Sari (International Conference On Law, Business and Governance (ICon-LBG), 2016)
The development of Sharia bank in Indonesia is very rapid. It is characterized by many conventional banks opening Islamic business units. All this makes the banking institutions vying to attract the hearts of investors to save their funds. So therefore the bank should be able to maintain customer confidence by way strive for the bank in a liquid state. If a banking institution in the state of illiquid it is certain that it is not healthy.The purpose of this study was to analyze the development of liquidity on BNI Sharia Yogyakarta branch of 2008-2010 as well as to analyze the influence of the number of customers and third party funds (DPK) for the provision of cash. Methodology of this study uses secondary data obtained from the literature that comes from books that discuss the object of study as well as related documentation on the subject of the research object. Data analysis techniques used in this research by using quantitative and qualitative methods consisting of analysis on the development of liquidity as well as multiple regression analysis.The results of the study of the growing amount of cash by using cash ratio that is increased and decreased in each month, on average they held cash amounting to 179 billion. For the development of the number of customers amounted to an average of 28 551 and third party fund its average value amounted to 15 trillion. From the results of multiple regressions it is known that the number of customers does not affect the variable provision of cash while third party funds affect the supply of cash in BNI Sharia of Yogyakarta branch.